2022
DOI: 10.1101/2022.06.27.497855
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hepatocytes deficient in nuclear envelope protein lamina-associated polypeptide 1 are an ideal mammalian system to study intranuclear lipid droplets

Abstract: Lipid droplets (LDs) are generally considered to be synthesized in the ER and utilized in the cytoplasm. However, LDs have been observed inside nuclei in some cells, although recent research on nuclear LDs has focused on cultured cell lines. To better understand nuclear LDs that occur in vivo, here we examined LDs in primary hepatocytes from mice following depletion of the nuclear envelope protein lamina-associated polypeptide 1 (LAP1). Microscopic image analysis showed that LAP1-depleted hepatocytes contain f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…The presence of nLDs in various species, including yeast, nematode, mouse, and human cells (Jin et al, 2020;R and P, 2013;Romanauska and Koehler, 2021;Romanauska and Kohler, 2018;Soltysik et al, 2019;Soltysik et al, 2021),has sparked interest in their origin and functions. Notably, the number of nLDs significantly increases in specific environments, such as in hepatocytes of mice with NAFLD (Ostlund et al, 2022;Shin et al, 2019). Recent studies have shown that the intranuclear membrane synthesizes lipids and serves as the site of nLD generation (Romanauska and Kohler, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of nLDs in various species, including yeast, nematode, mouse, and human cells (Jin et al, 2020;R and P, 2013;Romanauska and Koehler, 2021;Romanauska and Kohler, 2018;Soltysik et al, 2019;Soltysik et al, 2021),has sparked interest in their origin and functions. Notably, the number of nLDs significantly increases in specific environments, such as in hepatocytes of mice with NAFLD (Ostlund et al, 2022;Shin et al, 2019). Recent studies have shown that the intranuclear membrane synthesizes lipids and serves as the site of nLD generation (Romanauska and Kohler, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, conditions of elevated unsaturated fatty acids or impaired cellular phosphatidylcholine synthesis have led to the emergence of nLDs Kohler, 2018, 2021;Soltysik et al, 2019;Soltysik et al, 2021). The importance of these dynamics is emphasized by observations of abnormal nLD formation in pathological conditions, such as nonalcoholic fatty liver disease (NAFLD), a widespread and often debilitating condition that links disrupted cellular lipid metabolism with nLD formation (Ostlund et al, 2022;Shin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%